The critical role of interleukin-6 in protection against neurotropic flavivirus infection - Auroni, Tabassum T.; Arora, Komal; Natekar, Janhavi P.; Pathak, Heather; Elsharkawy, Amany; Kumar, Mukesh (Frontiers in Cellular and Infection Microbiology, 2023)
West Nile virus (WNV) and Japanese encephalitis virus (JEV) are emerging mosquito-borne flaviviruses causing encephalitis globally. No specific drug or therapy exists to treat flavivirusinduced neurological disease. The lack of specific therapeutics underscores an urgent need to determine the function of important host factors involved in flavivirus replication and disease progression. Interleukin-6 (IL-6) upregulation has been observed during viral infections in both mice and humans. Herein, we investigated the function of IL-6 in the pathogenesis of neurotropic flavivirus infections.First, we examined the role of IL-6 in flavivirus-infected human neuroblastoma cells, SK-N-SH, and found that IL-6 neutralization increased the WNV or JEV replication and inhibited the expression of key cytokines. We further evaluated the role of IL-6 by infecting primary mouse cells derived from IL-6 knockout (IL-6 −/− ) mice and wild-type (WT) mice with WNV or JEV. The results exhibited increased virus yields in the cells lacking the IL-6 gene. Next, our in vivo approach revealed that IL-6 −/− mice had significantly higher morbidity and mortality after subcutaneous infection with the pathogenic WNV NY99 or JEV Nakayama strains compared to WT mice. The non-pathogenic WNV Eg101 strain did not cause mortality in WT mice but resulted in 60% mortality in IL-6 −/− mice, indicating that IL-6 is required for the survival of mice after the peripheral inoculation of WNV or JEV. We also observed significantly higher viremia and brain viral load in IL-6 −/− mice than in WT mice. Subsequently, we explored innate immune responses in WT and IL-6 −/− mice after WNV NY99 infection. Our data demonstrated that the IL-6 −/− mice had reduced levels of key cytokines and chemokine in the serum of IL-6 −/− mice during early infection but elevated levels of proinflammatory cytokines and chemokines in the brain later, along with suppressed anti-inflammatory cytokines. In addition, mRNA expression of IFN-α and IFN-β was significantly lower in the infected IL-6 −/− mice. In conclusion, these data suggest that the lack of IL-6 exacerbates WNV or JEV infection in vitro and in vivo by causing an increase in virus replication and dysregulating host immune response.